Cervical vertebral maturation stage and Demirjian index for assessment of skeletal and dental maturation for children’s growth stages - Pradopo, Seno; Nuraini, Prawati; Rahmawati, Luluk; Ibrahim, Zurairah (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Determining age is essential in various fields, particularly pediatric dentistry. A reliable method for assessing an individual's growth and development involves evaluating their chronological and biological age. Biological age can be determined by examining skeletal or dental maturation. Accurately assessing growth potential and timing of growth spurts is crucial for several clinical situations, especially in the planning and outcomes of treatments like orthodontic therapy. Purpose: This study uses common radiographic ortho-diagnosis techniques to analyze the accuracy of cervical vertebral maturation stages (CVMS) and the Demirjian index methods in evaluating children's growth and development stages. Methods: The CVMS assessment on cephalometric radiography was conducted using the Bacetti method, which includes six stages. In addition, the mandibular second molars' calcification stages were evaluated using the Demirjian index method, which encompasses stages A to H on panoramic radiography. Following this, skeletal and dental maturation accuracy was analyzed using the Statistical Package for Social Sciences application. Results: This study revealed differences in the chronological age corresponding to each stage of calcification of the mandibular second molars and the CVMS. Additionally, CVMS was found to be the most accurate method for assessing age in children. Furthermore, the right side was generally preferred over the left at the calcification stages of the mandibular second molars. Conclusion: Using CVMS to assess skeletal maturation provides a more accurate determination of growth and developmental stages in children than the Demirjian index.